Formation, regeneration, and transformation of protoplasts of Streptomyces diastatochromogenes 1628 - Ma, Zheng; Liu, Jinxiu; Lin, Xiaozhen; Shentu, Xuping; Bian, Yalin; Yu, Xiaoping (Folia microbiologica, 2014)
Toyocamycin exhibits effective biological activities for use against plant pathogenic fungi thanks to its structural similarity to nucleoside. It has been recognized as a promising agricultural antibiotic utilized in controlling the occurrence of plant diseases. In our previous study, a strain that was isolated was identified and designated as Streptomyces diastatochromogenes whose major secondary metabolite was toyocamycin, but the production was largely limited. Protoplast transformation is a useful technique in the improvement of streptomycete. In this study, we optimized some key factors necessary for protoplast formation, regeneration, and transformation of S. diastatochromogenes. When mycelium was cultivated in CP medium with 1 % glycine, harvested at 48 h old, and then treated with 3 mg lysozyme/mL in P buffer for 1 h, the greatest regeneration frequency (42.5 %) of protoplasts was obtained. By using 1 × 10(9)/mL protoplasts with polyethylene glycol 1000 at a concentration of 30 % (w/v), the best performance of protoplast transformation efficiency was 4.8 × 10(3)/μg DNA transformants.
Keywords: protoplasty; Protoplasts; kultivační média; bakteriologické techniky; Culture Media; Transformation, Bacterial; bakteriální transformace; Bacteriological Techniques; Streptomyces